Resolving medical malpractice disputes through customary institutions: Between statutory law and local wisdom - Novi Afsari; Avy Permata Sari; Fatmasari Diahpermata Djajaputri Adhimutiahara; Ida Bagus Gede Adiguna Wibawa; Carolina Kuntardjo (Institute of Computer Science (IOCS), 2026)
The transformation of medical dispute resolution in Indonesia reveals a critical paradox: while Law No. 17 of 2023 on Health mandates non-litigation mechanisms, the existing framework remains entrapped within a state-centric legal paradigm that systematically marginalizes customary institutions which have long served as accessible, socially legitimate, and restoratively-oriented dispute forums across diverse Indonesian communities. A fundamental research gap persists in the prevailing legal monism approach, which creates a normative vacuum by failing to recognize customary institutions operationally within health law, thereby forcing communities to choose between legally certain but inaccessible formal mechanisms and socially accepted but legally uncertain customary processes — a justice gap that disproportionately burdens economically vulnerable populations. This study employs a normative-prescriptive legal methodology integrating legislative, conceptual, and comparative approaches to reconstruct the positional framework of customary institutions within medical dispute resolution. The findings reveal that customary institutions hold strong constitutional legitimacy under Article 18B(2) of the 1945 Constitution yet operate within a normative vacuum in the medical domain, and introduce a Two-Tier Integrative Model positioning customary institutions as relational mediation forums at the first tier and MKDKI as technical verifier at the second tier, connected through a court homologation mechanism. This study provides a strategic normative blueprint recommending explicit revision of Law No. 17 of 2023 to accommodate customary institutions within the national medical dispute resolution system.